(untitled) (Eurasian Journal of Engineering and Technology, 2025)
This comprehensive article examines the transformative impact of the information revolution on global geopolitics, with particular attention to the role of mass media and virtual technologies in shaping political narratives, national identity, and international security. It explores the strategic importance of the Commonwealth of Independent States (CIS) as a unified geopolitical space, particularly in the context of hybrid threats such as information warfare, ideological influence, and media manipulation. The analysis highlights how modern communication tools—especially television and the internet—have become powerful instruments in shaping public opinion, promoting geopolitical agendas, and influencing state behavior. Drawing on examples from global media giants such as CNN, BBC, and Reuters, the article underscores the shifting parameters of security and the growing relevance of media literacy and geopolitical awareness in the digital age